They have Verve: Preservice Teachers' Perceptions about Culturally Relevant/Responsive Pedagogy. Issue 2 (3rd April 2018) - Nash, Kindel
ABSTRACT: Based on concerns about the permanence of racism in our society and its impact on opportunities for children's equitable education, this empirical study used narrative inquiry to explore four preservice teachers' developing dispositions as they studied and implemented culturally relevant/responsive pedagogy (CR/RP) in an early literacy education course framed by critical race theory. Whereas the majority of publications based on this study's findings have focused on preservice teachers' problematic white racial discourse showcasing narrative profiles, this article focuses on a finding that opportunities to study race and CR/RP led the preservice teachers to new perceptions about culturally relevant/responsive pedagogy, race, and racism. Yet, within these purported learnings, preservice teachers' continued use of white racial discourse points to the need for teacher educators to engage preservice teachers in contextualized discussions about the social, political, economic, and historical roots of racism.